2018
DOI: 10.1002/psc.3091
|View full text |Cite
|
Sign up to set email alerts
|

A general method for preparation of N‐Boc‐protected or N‐Fmoc‐protected α,β‐didehydropeptide building blocks and their use in the solid‐phase peptide synthesis

Abstract: N-(tert-butyloxycarbonyl) or N-(9-fluorenylmethoxycarbonyl) dipeptides with C-terminal (Z)-α,β-didehydrophenylalanine (∆ Phe), (Z)-α,β-didehydrotyrosine (∆ Tyr), (Z)-α,β-didehydrotryptophan (∆ Trp), (Z)-α,β-didehydromethionine (∆ Met), (Z)-α,β-didehydroleucine (∆ Leu), and (Z/E)-α,β-didehydroisoleucine (∆ Ile) were synthesised from their saturated analogues via oxidation of intermediate 2,5-disubstituted-oxazol-5-(4H)-ones (also known as azlactones) with pyridinium tribromide followed by opening of the produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…A brief survey of conditions revealed that serviceable yields of tetrapeptide 3a could be obtained by first hydrolyzing the azlactone through treatment with NaOH and then employing PyBOP to mediate coupling with Ala-OMe. 34 Construction of variant 3b wherein the Aib-3 residue of 1 is replaced by ΔAla is summarized in Scheme 5. Hydrogenolysis of the dipeptide Cbz-Ser-Ala-OMe (16) was followed by coupling with dipeptide 13, furnishing tetrapeptide 17 in moderate yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief survey of conditions revealed that serviceable yields of tetrapeptide 3a could be obtained by first hydrolyzing the azlactone through treatment with NaOH and then employing PyBOP to mediate coupling with Ala-OMe. 34 Construction of variant 3b wherein the Aib-3 residue of 1 is replaced by ΔAla is summarized in Scheme 5. Hydrogenolysis of the dipeptide Cbz-Ser-Ala-OMe (16) was followed by coupling with dipeptide 13, furnishing tetrapeptide 17 in moderate yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ring opening and coupling of the hindered azlactone intermediate was difficult. A brief survey of conditions revealed that serviceable yields of tetrapeptide 3a could be obtained by first hydrolyzing the azlactone through treatment with NaOH and then employing PyBOP to mediate coupling with Ala-OMe …”
Section: Resultsmentioning
confidence: 99%
“…Boc-SPPS uses trifluoroacetic acid solution to remove the amine protection groups and hydrogen fluoride solution to cleave the final peptide, but these processes are associated with irritating odor and toxicity. Fmoc can be removed under milder conditions, and the Fmoc-SPPS strategy is thus often preferred 120 . However, Boc-SPPS has advantages for long peptide synthesis, because trifluoroacetic acid deprotection effectively destroys the aggregation during the peptide synthesis 121 .…”
Section: Chemical Synthesis Of Peptidesmentioning
confidence: 99%
“…Non-proteinogenic α,β-didehydro-α-amino acids, with peculiar conformational properties-planar conformation due to a double bond, between Cα and Cβ carbon atoms and fixed values of t φ and ψ torsion angles, have shown their ability to form hydrogels (Vilaça et al, 2015b) and applicable in drug delivery. A procedure for cheaper, less laborious and less time taken than other methods of dehydropeptide synthesis (α,β-didehydro-α-amino acid) through oxidation of the C-terminal residue in N-Boc-protected and N-Fmocprotected peptides, both in solution and on the solid support for peptide synthesis has been reported by Wołczanski and Lisowski (Wołczanski and Lisowski, 2018). The ability to form secondary and super secondary structures and highly stable nanostructures has made α,β-didehydrophenylalanine a center of attraction for the researchers (Gupta and Chauhan, 2011).…”
Section: Dipeptides For Biologics Deliverymentioning
confidence: 99%